Assessment of Barriers and Opportunities Using Gender and Roma Lens in North Macedonia : Case of Transport - World Bank (World Bank, Washington, DC, 2020)
Building and maintaining roads can have significant economic and social benefits in terms of economic growth and increased access to jobs and to a range of services citizens depend on. However, road infrastructure and transport services are often mistakenly assumed to have uniform benefits for everyone, but they are, in fact, differently experienced by different population groups. For example, women and men often have varying needs for transport infrastructure and services, which stem from their different productive and reproductive roles they hold in a society. At the same time, women and men are not homogenous and they experience transport differently due to their different socio-economic and demographic features, such as, income, age, disabilities, ethnicity and/or location. These multiple identities often lead to multiple and overlapping disadvantages for many, commonly known as ‘intersectionality1’- influencing access to and use of services and economic opportunities of the multiple identity holders differently. As an example, a Roma woman could face several mobility disadvantages for being women and being a member of a socially excluded group. This assessment was undertaken as part of the World Bank financed North Macedonia Local Roads Connectivity Project (‘the Project’) to explore, for the first time, the less-studied situation of social inclusion in a transport project along gender and ethnicity lines in the country. The assessment (i) identified specific needs of Roma women, Roma men and non-Roma women for road infrastructure and public transport, (ii) explored their needs, experiences and aspirations towards the employment in the sector, and (iii) defined entry points for the Project to address some of these needs. The Roma2 are the largest ethnic minority in Europe, as well as one of the most deprived and socially excluded groups. At the same time, women, in general, tend to face different or more acute mobility barriers compared to men. Also, fewer women than men are employed in the transport sector, which is traditionally male dominated. Therefore, it was decided to apply intersectional lens to the analysis to understand mobility and employment barriers that Roma women, Roma men and non-Roma women are facing in order to bring out more nuances of social exclusion and better tailor the solutions to the project.